Le Brésil et ses Indiens : une réconciliation impossible ? - François-Michel Le Tourneau (EchoGéo)
The 1988 Constitution of Brazil, which recognizes extensively indigenous land rights, seemed to make possible the reparation of the historical prejudice represented by the territorial dispossession of Indigenous peoples. However, after 30 years, the reconciliation did not take place. Vast swaths of Brazil (about 12.3%) were recognized as Indigenous territories, but land conflicts are still acute. The political and social contexts have changed much in the last 10 years, leading to a renewed contestation of claimed but also already established indigenous lands. This paper analyzes the current situation and what is at stake with the many legislative projects under review. To that end, we first sketch a rapid history of how indigenous rights were considered throughout Brazilian history. We then show how the advances linked with the 1988 Constitution have permitted the constitution of a vast amount of “indigenous lands”, even if the indigenous population of Brazil only amounts to a very small fraction of Brazilian population. Last, we turn to the current situation and show how indigenous land rights have been more and more contested from 2005 on and how their juridical and physical protection is deeply challenged. In conclusion, we try to trace what future evolution on this topic might be.